2019
DOI: 10.1021/acs.iecr.9b01395
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Treatment Strategies Based on Hydrodynamic Cavitation, Advanced Oxidation Processes, and Aerobic Oxidation for Efficient Removal of Naproxen

Abstract: Removal of naproxen (NAP) present in wastewater has been studied using an improved approach based on hydrodynamic cavitation (HC), combined with ozone or hydrogen peroxide as pretreatment for biological oxidation. Initially, the operating conditions for pretreatment based on HC reactor has been optimized as an inlet pressure of 4 bar and pH 3, where the maximum extents of degradation of NAP (28.9%) and chemical oxygen demand (COD) reduction (11.3%) were achieved using the approach of HC operated individually. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 43 publications
0
17
0
4
Order By: Relevance
“…Вступ. Кавітація та її комбінації з іншими методами -основа ефективних технологій очищення стічних вод від дисперсних твердих частинок [1,2] та шкідливих органічних сполук [3][4][5][6][7][8][9][10]. Так, встановлено, що максимальної швидкості флотації кальцію оксалату, який утворювався внаслідок хімічної взаємодії натрію оксалату (протрава під час дублення шкіри) із кавітаційно активованими дисперсними частинками суспензії кальцію гідроксиду, досягали за тривалості кавітаційного оброблення 600…900 с і тиску на вході у гідродинамічний кавітатор 0,3…0,4 МПа [1].…”
Section: кавітація у комбінованих технологіях очищення стічних вод віunclassified
See 2 more Smart Citations
“…Вступ. Кавітація та її комбінації з іншими методами -основа ефективних технологій очищення стічних вод від дисперсних твердих частинок [1,2] та шкідливих органічних сполук [3][4][5][6][7][8][9][10]. Так, встановлено, що максимальної швидкості флотації кальцію оксалату, який утворювався внаслідок хімічної взаємодії натрію оксалату (протрава під час дублення шкіри) із кавітаційно активованими дисперсними частинками суспензії кальцію гідроксиду, досягали за тривалості кавітаційного оброблення 600…900 с і тиску на вході у гідродинамічний кавітатор 0,3…0,4 МПа [1].…”
Section: кавітація у комбінованих технологіях очищення стічних вод віunclassified
“…Ефективність деградації забруднювачів визначається їх початковою концентрацією у рідині (воді) [3], величиною pH [4], реаґентним режимом [4,5], енергетичними характеристиками кавітаційного оброблення (питомою потужністю ультразвукових генераторів, тиском на вході у гідродинамічні кавітатори) [6][7][8], а також конструктивними особливостями кавітаційних апаратів [9,10].…”
Section: кавітація у комбінованих технологіях очищення стічних вод віunclassified
See 1 more Smart Citation
“…In recent years, cavitation technology has been widely used for the degradation of organic wastewater, purification of drinking water, hydrolysis of oils, and strengthening of biodiesel synthesis. Thanekar et al 15 have studied the treatment of naproxen (NAP) in wastewater with combined HC and oxidants (HC + O 3 ). They found that the best HC + O 3 pretreatment method can reduce chemical oxygen demand (COD) by 40%, and the sewage that is further treated with activated HC + O 3 has reduced COD by about 89.5%.…”
Section: Introductionmentioning
confidence: 99%
“…Some applications not envisaged at the time of the call are also seen (for example, a cook stove as a fluidic device without any moving parts). The contributions in this special issue may be broadly classified into four groups: Microfluidics/microreactors Coils, curved channels, and inserts Specialized fluidic devices Other …”
mentioning
confidence: 99%